2018
DOI: 10.1111/evo.13470
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid chickadees are deficient in learning and memory

Abstract: Identifying the phenotypes underlying postzygotic reproductive isolation is crucial for fully understanding the evolution and maintenance of species. One potential postzygotic isolating barrier that has rarely been examined is learning and memory ability in hybrids. Learning and memory are important fitness-related traits, especially in scatter-hoarding species, where accurate retrieval of hoarded food is vital for winter survival. Here, we test the hypothesis that learning and memory ability can act as a post… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 71 publications
3
77
3
Order By: Relevance
“…Learning and memory have also been linked to postzygotic isolation since deficiencies in these traits can be selected against in hybrids (Rice & McQuillan, ). Recently, McQuillan, Roth, Huynh, and Rice () found that hybrid chickadees scored lower than parental chickadees in associative spatial learning and problem‐solving tasks. Learning and memory have been implicated in goal‐oriented foraging behaviour in Neotropical primates (Garber, ; Janson, ), traits presumably important for howler monkeys, which maintain a predominantly folivorous–frugivorous diet in highly diverse tropical forests where they adjust their dietary intake on seasonal availability of preferred foods (Raño, Kowalewski, Cerezo, & Garber, ).…”
Section: Discussionmentioning
confidence: 99%
“…Learning and memory have also been linked to postzygotic isolation since deficiencies in these traits can be selected against in hybrids (Rice & McQuillan, ). Recently, McQuillan, Roth, Huynh, and Rice () found that hybrid chickadees scored lower than parental chickadees in associative spatial learning and problem‐solving tasks. Learning and memory have been implicated in goal‐oriented foraging behaviour in Neotropical primates (Garber, ; Janson, ), traits presumably important for howler monkeys, which maintain a predominantly folivorous–frugivorous diet in highly diverse tropical forests where they adjust their dietary intake on seasonal availability of preferred foods (Raño, Kowalewski, Cerezo, & Garber, ).…”
Section: Discussionmentioning
confidence: 99%
“…We genotyped all birds at 10 species-diagnostic single nucleotide polymorphism markers (McQuillan et al, 2017). We ran STRUCTURE on this larger dataset of over 400 total genotypes using the same program settings as McQuillan et al (2017McQuillan et al ( , 2018 To do this, we combined the genotypes of our test subjects with a larger dataset from multiple Pennsylvania hybrid-zone populations, as well as known pure-species individuals from allopatric populations of both species (New York and Louisiana, USA).…”
Section: Genetic Determination Of Species Ancestrymentioning
confidence: 99%
“…However, postzygotic reproductive barriers are present. Hybrid chickadees also are less likely to solve novel problems (McQuillan et al, 2018). Additional costs to hybridization are also found in adult birds of mixed ancestry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations